2018
DOI: 10.1016/j.palaeo.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Nam Lot (MIS 5) and Duoi U'Oi (MIS 4) Southeast Asian sites revisited: Zooarchaeological and isotopic evidences

Abstract: The Nam Lot site in Laos and the hominin-bearing Duoi U'Oi site in Vietnam are dated to MIS 5 (86-72 ka) and MIS 4 (70-60 ka), respectively. Located in the same latitudinal belt ~20°N in the north of the Indochinese area, the faunal assemblages recovered from breccia deposits in a karstic context have the potential to provide information on the palaeoenvironmental conditions faced by earliest modern humans when they entered the Southeast Asian mainland. Here, zooarchaeological evidence of faunas are reviewed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 160 publications
1
37
0
1
Order By: Relevance
“…While Chinese speleothems provide high‐resolution proxy records of precipitation for the wider region, the resulting effects on landscape‐ to site‐scale palaeoenvironments remain poorly resolved, due to the limited preservation of traditional palaeoecological proxies and the complex environmental mosaics that characterise MSEA (Wurster & Bird, ). While MIS 3 and MIS 4 were characterised by relatively open environments across much of Sundaland (Hunt et al, ; Wurster & Bird, ), faunal evidence from Laos and Vietnam suggests forest species persisted there under humid conditions (Bacon et al, ; Milano et al, ), with arid conditions leading to an expansion of open environments during MIS 2 at Tam Pa Ling, Laos. Marwick and Gagan () characterise MIS 3 at Tham Lod rockshelter, Thailand, as a period of wetter and more unstable conditions than MIS 2, while Hunt et al () inferred more open environments during MIS 2 at Niah Cave in Borneo and Wurster et al () reported a spatially varied pattern of climate‐driven forest contraction across Pleistocene Sundaland.…”
Section: Con Moong Cave: Climatic Geomorphological and Archaeologicamentioning
confidence: 99%
“…While Chinese speleothems provide high‐resolution proxy records of precipitation for the wider region, the resulting effects on landscape‐ to site‐scale palaeoenvironments remain poorly resolved, due to the limited preservation of traditional palaeoecological proxies and the complex environmental mosaics that characterise MSEA (Wurster & Bird, ). While MIS 3 and MIS 4 were characterised by relatively open environments across much of Sundaland (Hunt et al, ; Wurster & Bird, ), faunal evidence from Laos and Vietnam suggests forest species persisted there under humid conditions (Bacon et al, ; Milano et al, ), with arid conditions leading to an expansion of open environments during MIS 2 at Tam Pa Ling, Laos. Marwick and Gagan () characterise MIS 3 at Tham Lod rockshelter, Thailand, as a period of wetter and more unstable conditions than MIS 2, while Hunt et al () inferred more open environments during MIS 2 at Niah Cave in Borneo and Wurster et al () reported a spatially varied pattern of climate‐driven forest contraction across Pleistocene Sundaland.…”
Section: Con Moong Cave: Climatic Geomorphological and Archaeologicamentioning
confidence: 99%
“…Our stable isotope results also indicate that C. sumatraensis has been well-adapted to variable environmental conditions expanding from closed C 3 to open C 4 landscapes since the Middle Pleistocene and has been a generalist with a greater ecological flexibility in diet and habitat than both Pleistocene and extant Naemorhedus (Figures 2, 4). Although some isotopic data from well-dated localities such as Khok Sung (MIS7 or MIS5) (Suraprasit et al, 2018;Duval et al, 2019;this study) and Nam Lot (MIS5) (Bacon et al, 2018b) as well as from the Early Holocene of Ban Rai Rockshelter have documented the preferred habitat restriction of the Sumatran serows in closed forest environments (Figure 2), this might be explained by the sampling bias for which few specimens are available or analyzed or by the ecological adaptation of C. sumatraensis in response to more homogeneous and closed conditions during interglacial stages. In the heterogeneous environments during the Pleistocene, C. sumatraensis preferably occupied in both closed forest and open grassland landscapes but rarely in an intermediate area between these two canopies.…”
Section: Discussion Evolutionary Niche Differentiation and Adaptationmentioning
confidence: 92%
“…For the isotope comparison between large herbivores and predators, the fractionation factor of δ 13 C values for carnivores is adjusted by +1.3 (Clementz et al, 2009;Domingo et al, 2013). The faunal isotope baseline includes previously analyzed enamel samples from Pha Bong (Bocherens et al, 2017), Khok Sung (Suraprasit et al, 2018), and Tham Wiman Nakin (Pushkina et al, 2010;Bocherens et al, 2017) in Thailand, Nam Lot (Bacon et al, 2018b) in Laos, and Boh Dambang in Cambodia (Bacon et al, 2018c) (see Supplementary Material S4 for raw data).…”
Section: Discussion Evolutionary Niche Differentiation and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the fossil record of Hylochoerus is very sparse. The only securely dated and well-identified fossils of Hylochoerus are those from Member III of the Kibish Formation ~0.1 Ma (Figure 1, Assefa et al 2008). Therefore, the past diversity of Hylochoerus and the evolution of its derived craniomandibular and dental traits remain uncharted.…”
Section: Introductionmentioning
confidence: 99%